2014
DOI: 10.1120/jacmp.v16i1.5108
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of daily interfractional larynx residual setup error after isocentric alignment for head and neck radiotherapy: quality assurance implications for target volume and organs‐at‐risk margination using daily CT on‐rails imaging

Abstract: Larynx may alternatively serve as a target or organ-at-risk (OAR) in head and neck cancer (HNC) image-guided radiotherapy (IGRT). The objective of this study was to estimate IGRT parameters required for larynx positional error independent of isocentric alignment and suggest population–based compensatory margins. Ten HNC patients receiving radiotherapy (RT) with daily CT-on-rails imaging were assessed. Seven landmark points were placed on each daily scan. Taking the most superior anterior point of the C5 verteb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 46 publications
(59 reference statements)
0
13
0
Order By: Relevance
“…We previously reported that small volume IMRT for T1 glottic cancer requires rigorous patient evaluation, radiation planning, delivery, monitoring, and quality assurance . This includes laryngoscopic examination, multidisciplinary surgical/radiotherapist evaluation of tumor extent, high‐resolution angled axial computed tomography examination for evaluation of occult extension, careful target delineation, evaluation of glottic motion, rigorous clinical and physics quality assurance, and in‐treatment image guidance …”
Section: Discussionmentioning
confidence: 99%
“…We previously reported that small volume IMRT for T1 glottic cancer requires rigorous patient evaluation, radiation planning, delivery, monitoring, and quality assurance . This includes laryngoscopic examination, multidisciplinary surgical/radiotherapist evaluation of tumor extent, high‐resolution angled axial computed tomography examination for evaluation of occult extension, careful target delineation, evaluation of glottic motion, rigorous clinical and physics quality assurance, and in‐treatment image guidance …”
Section: Discussionmentioning
confidence: 99%
“…In a programmatic effort to define normal tissue[18, 3335] and tumor response [36] profiles that include gradient-dose representation, future efforts are focused on determining not only DVH-based (2D) volumetric representations of dose, but include developing efforts at 3D-dose deposition differentials across mandibular sub-volumes using validated image-registration platforms[37]. Likewise, while this dataset, in contrast to previously presented salivary gland patient series[38], focused exclusively on oropharyngeal cancer patients in order to isolate a comparatively uniform treatment paradigm (e.g., avoiding cases with therapeutic oral cavity surgery as a confounder); future efforts will be directed at construction of comprehensive dose response models, including more elaborate classifiers of potential risk strata.…”
Section: Discussionmentioning
confidence: 99%
“…Otherwise, in the aspect of interfraction set-up error, we used 3-mm PTV expansions margins with weekly portal films. Some studies reported that 5-mm margin is needed to compensate the setup error if the larynx is a target, and usually verified the larynx motion by daily image such as portal films or in room CT [ 14 18 22 ]. However, by analyzing the log files of the couch movement after the acquisition of weekly portal films, we observed that weekly couch variation was within 3 mm (mean, 2.3 ± 0.8).…”
Section: Discussionmentioning
confidence: 99%